Copper-Catalyzed Nitrogenation of Aromatic and Aliphatic Aldehydes: A Direct Route to Carbamoyl Azides - Wei, Rongbiao; Ge, Liang; Bao, Hongli; Liao, Saihu; Li, Yajun (Synthesis, 2019)
An efficient copper-catalyzed synthesis of carbamoyl azides directly from aldehydes has been developed. Both aromatic aldehydes and aliphatic aldehydes, together with other commercially available reactants, can be used as substrates in this radical relay reaction. Broad substrate scope, simple operation, readily available reagents, and good functionality tolerance make this method very attractive.
Keywords: copper catalyst; carbamoyl azides; aromatic aldehydes; aliphatic aldehydes; nitrogenation; radical